Hydrogel Micropillars: Clustering and Self‐Recovery of Slanted Hydrogel Micropillars (Adv. Mater. Interfaces 24/2018). Issue 24 (20th December 2018) - Lee, Hyemin; Kim, Jun‐Hyun; Wu, Gaoxiang; Lee, Hae‐Min; Kim, Jaekyoung; Kwon, Dokyeong; Yang, Shu; Kim, Chang‐Koo; Yoon, Hyunsik
Abstract : In article number1801142 Hyemin Lee, Chang‐Koo Kim, Hyunsik Yoo, and co‐workers present a sequential recovery of clustered slanted hydrogel pillars to their original shape by exploiting the modulus change of hydrogel materials during water evaporation. The clustering and recovery of the slanted hydrogel micro‐pillars are monitored in situ by optical microscopy and environmental scanning electron microscopy. By using a simple model, the authors explain the mechanism of sequential behavior.